JURIDICAL ANALYSIS OF CENTRAL RELATIONS BETWEEN VILLAGE ADMINISTRATION AND BPD IN VILLAGE DEVELOPMENT - Sri Sudono Saliro; Karman Karman; Wahyu Firmansyah (DE'RECHTSSTAAT, 2022)
Institutional and government structures at all levels of government, village government must be directed to be able to create a government that is sensitive to developments and changes that occur in society. Therefore, a synergy relationship is needed between the village government, BPD, the community, and others to support village development. The focus of research is how the role of village government and BPD in village development according to Law no. 6 of 2014 concerning the Village in Sepuk Tanjung Village, Sebawi District, and what factors support the village government and the BPD in carrying out government relations in order to increase village development in the village. The results of the study concluded that the relationship between the village government and the BPD in the scope of development of Sepuk Tanjung Village has a very central role, but there are factors that become the village government and the BPD in implementing village development.